2019
DOI: 10.3390/ijerph16071249
|View full text |Cite
|
Sign up to set email alerts
|

Setting-Specific and Symptom-Specific Association between Secondhand Smoke Exposure and Depressive Symptoms

Abstract: Few studies have focused on the potential relationship between secondhand smoke (SHS) exposure and depressive symptoms. This study aimed to explore the potential association between SHS exposure and depressive symptoms and differentiate this association in setting-specific exposure and symptom-specific outcomes. A cross-sectional study was conducted in Guangdong province of China from September to December 2010 using a multistage sampling method to randomly sample adults aged 18 years and older. SHS exposure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For example, harmful determinants can influence the uptake of risk behaviours. Risk behaviours, such as sedentary behaviour, substance abuse and smoking/nicotine exposure, have been linked to depression [ 226 , 335 , 355 , 385 , 386 , 387 , 388 , 389 , 390 , 391 , 392 , 393 , 394 , 395 , 396 , 397 , 398 , 399 , 400 , 401 ]. Harmful determinants can also have an impact on diet.…”
Section: Resultsmentioning
confidence: 99%
“…For example, harmful determinants can influence the uptake of risk behaviours. Risk behaviours, such as sedentary behaviour, substance abuse and smoking/nicotine exposure, have been linked to depression [ 226 , 335 , 355 , 385 , 386 , 387 , 388 , 389 , 390 , 391 , 392 , 393 , 394 , 395 , 396 , 397 , 398 , 399 , 400 , 401 ]. Harmful determinants can also have an impact on diet.…”
Section: Resultsmentioning
confidence: 99%
“…Third, we did not stratify the causal association between SHS and potential diseases by gender and subtype, although some studies suggested that may affect the causality. Some studies suggested SHS may have dose-response relationships with specific symptoms, 36 of which we did not compare in our study. Moreover, because the SNPs identified have a small variance, the effect of most of them is moderate, 37 which means a more reliable instrument and more samples are needed for more precise results.…”
Section: Discussionmentioning
confidence: 76%